Applications of phase change materials in smart drug delivery for cancer treatment - Bao, Jianfeng; Tu, Hui; Li, Jing; Li, Yijia; Yu, Shan; Gao, Jingpi; Lei, Kun; Zhang, Fengshou; Li, Jinghua (Frontiers in Bioengineering and Biotechnology, 2022)
Phase change materials (PCMs) are materials that are stimulated by the external enthalpy change (temperature) to realize solid-liquid and liquid-solid phase transformation. Due to temperature sensitivity, friendly modification, and low toxicity, PCMs have been widely used in smart drug delivery. More often than not, the drug was encapsulated in a solid PCMs matrix, a thermally responsive material. After the trigger implementation, PCMs change into a solid-liquid phase, and the loading drug is released accordingly. Therefore, PCMs can achieve precise release control with different temperature adjustments, which is especially important for small molecular drugs with severe side effects. The combination of drug therapy and hyperthermia through PCMs can achieve more accurate and effective treatment of tumor target areas. This study briefly summarizes the latest developments on PCMs as smart gate-keepers for anti-tumor applications in light of PCMs becoming a research hot spot in the nanomedicine sector in recent years.